Radio Dan Eksistensi Bahasa Daerah (Program Rampai Talang Banyuasin Di Radio Suara Indah Persada Fm) - Amilia Hikma Al-Umari; Indrawati; Ahmad Harun Yahya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
Radio Suara Indah Persada FM is a local radio station in Banyuasin since 2008. The presence of Radio Suara Indah Persada FM as a local radio that is able to maintain the existence of radio and its local language until now is not easy. There are many external and internal factors that affect the existence of Suara Indah Persada FM radio. This makes Radio Suara Indah Persada FM must have strategies in order to continue to maintain its existence, by always maintaining the Banyuasin regional language. Through the Rampai Talang Banyuasin (RTB) program, which received a KPI award as the best cultural Feature category in 2014. This research aims to find out what are the factors that affect the existence of radio and local languages in the Rampai Talang Banyuasin program, and to find out how the strategies carried out by Radio Suara Indah Persada FM in maintaining the existence of local languages through the Rampai Talang Banyuasin program, using Dimmick and Rothenbuhler's media ecology theory, they argue that to maintain its existence, the media needs three main sources of existence, namely capital (advertising revenue), type of content (type of media content) and type of audience (type of target audience). The method used in this research is descriptive qualitative method and data collection techniques using observation, interviews, and documents related to the research. The results showed that the factors that influence the existence of radio and local languages come from supporting factors and internal and external inhibiting factors. Radio Suara Indah Persada FM in maintaining the existence of radio and local languages through the Rampai Talang Banyuasin program, namely: 1) Carry out planning, production and purchase of programs, execution and supervision of the Rampai Talang Banyuasin program. 2) conducting segmentation, targeting, and posiotoning in capturing the audience market on Rampai Talang Banyuasin. 3) Marketing strategy in marketing Rampai Talang Banyuasin program.